Kecepatan Aus Cat Marka Jalan Akibat Lalu-Lintas dan Lingkungan Jalan di Kota Bandung - Nanny Kusminingrum; Leksminingsih Leksminingsih (Jurnal Jalan-Jembatan, 2005)
The use of road marking paint for safety of road users currently increased rapidly and with the use of high quality of road marking paints led to the reduce of traffic accidents. Based on field observation showed that preliminary ageing of road marking paints occurred. Research results of road marking paints of several road links in Bandung conducted at the end of 2001 with observation over the year of 2002, abration was found for the manual application (by hand brushing) with the abration percentage reached 100% during one year after application, using marking machines (compressor), the wearing reached 80% when the surface was well prepared and the paint was well laid (with compressor), loss of adhesion can be reduced to 50% over one year. Based on on observation, high traffic is the main cause of loss of adhesion compared to environmental factor measured i.e the average temperature on the pavement surface still below the softening point of asphalt